2003
DOI: 10.1016/s0042-6822(03)00207-1
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput gene expression profiling indicates dysregulation of intestinal cell cycle mediators and growth factors during primary simian immunodeficiency virus infection

Abstract: During primary simian immunodeficiency virus (SIV) infection, CD4+ T cells are severely depleted in gut-associated lymphoid tissue (GALT), while CD8+ T-cell numbers dramatically increase. To gain an understanding of the molecular basis of this disruption in T-cell homeostasis, host gene expression was monitored in longitudinal jejunum tissue biopsies from SIV-infected rhesus macaques by DNA microarray analysis. Transcription of cyclin E1, CDC2, retinoblastoma, transforming growth factor (TGF), fibroblast growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 29 publications
8
77
0
Order By: Relevance
“…Indeed, patients with heightened LPS levels showed substantially accelerated disease progression, with a median time to clinical event of 1.5 years, versus 4 years for patients with lower levels (41). As a possible complement to these findings, previous data strongly suggested a correlation between intestinal immune dysfunction and intestinal functionality, as suggested both by gene expression profiling that associated gut CD4 ϩ T-cell depletion with downregulated expressions of genes involved in mucosal function (110,111) and by earlier clinical data on malabsorption and nutritional complications in SIV-infected RM (111) and HIV-infected humans (112). Along the same lines, a nested-control study from the Strategies for Management of Anti-Retroviral Therapy (SMART) trial by Sandler et al reported that plasma levels of sCD14 are independent predictors of overall mortality in HIV disease (37).…”
Section: Clinical Implications Of Microbial Translocation In Hiv Disementioning
confidence: 88%
“…Indeed, patients with heightened LPS levels showed substantially accelerated disease progression, with a median time to clinical event of 1.5 years, versus 4 years for patients with lower levels (41). As a possible complement to these findings, previous data strongly suggested a correlation between intestinal immune dysfunction and intestinal functionality, as suggested both by gene expression profiling that associated gut CD4 ϩ T-cell depletion with downregulated expressions of genes involved in mucosal function (110,111) and by earlier clinical data on malabsorption and nutritional complications in SIV-infected RM (111) and HIV-infected humans (112). Along the same lines, a nested-control study from the Strategies for Management of Anti-Retroviral Therapy (SMART) trial by Sandler et al reported that plasma levels of sCD14 are independent predictors of overall mortality in HIV disease (37).…”
Section: Clinical Implications Of Microbial Translocation In Hiv Disementioning
confidence: 88%
“…4B) in intestinal mucosa that are required for normal maturation of enterocytes. In the SIV model, multiple growth factors as well as genes mediating intestinal epithelial (enterocyte) repair and regeneration have been shown to be dysregulated in GALT during primary acute and chronic stages of infection (6)(7)(8)(9)(10). Moreover, SIV-infected macaque studies have demonstrated impaired nutrient digestive and adsorptive functions during primary SIV infection (6).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from the tissue samples, and double-stranded cDNA was synthesized as described (8). Biotin-labeled cRNA was hybridized with Affymetrix U95Av2 GeneChips.…”
Section: Methodsmentioning
confidence: 99%
“…We inoculated four macaques (MK3, MK4, MK6 and MK10) intravenously with previously titrated frozen stocks of SIV mac251. We determined plasma viral loads as previously described 49 . Macaques were pre-anesthetized with ketamine (10 mg/kg; Parke- NIH-PA Author Manuscript NIH-PA Author Manuscript NIH-PA Author Manuscript Davis), followed by placement of an endotracheal tube and maintenance of the anesthesia with isofluorane.…”
mentioning
confidence: 99%